Oil, Gas, and Mining : A Sourcebook for Understanding the Extractive Industries - Cameron, Peter D. (Washington, DC: World Bank, 2017)
Oil, Gas, and Mining: A Sourcebook for Understanding the Extractive Industries provides developing countries with a technical understanding and practical options around oil, gas, and mining sector development issues.